The impact of combining pain education strategies with physical therapy interventions for patients with chronic pain: A systematic review and meta-analysis of randomized controlled trials - Marris, Danielle; Theophanous, Kyriakos; Cabezon, Pablo; Dunlap, Zachary; Donaldson, Megan (Physiotherapy theory and practice, 2021)
Study Design: Systematic Review with meta-analysis. Background: Rehabilitation providers have begun to incorporate pain education into their treatment protocols to influence the patient's experience and knowledge to improve their condition. The purpose of this systematic review is to determine if the addition of pain education strategies to physical therapy treatments is beneficial in reducing pain intensity and disability for those with chronic musculoskeletal pain. Methods: A systematic database search was conducted for randomized control trials that investigated the concurrent use of pain education and physical therapy. Standardized methods for article identification, inclusion, and quality appraisal was utilized. Where possible, studies were pooled for meta-analysis, with pain and disability as the primary outcomes. Results: Fourteen articles were included in this review, of which all fourteen were rated as high quality using the PEDro scale of quality assessment. Meta-analyses were conducted on pain and disability constructs at short term (< 12 weeks) and long-term (≥ 12 weeks) for the studies that allowed for quantitative pooling of effect sizes. Thirteen out of the fourteen included studies demonstrated a decrease in pain and disability with the use of combined interventions. There was a large effect on short-term pain (SMD 0.837), long-term pain (SMD 0.964), and long-term disability (SMD 1.374). A moderate effect on with short-term disability (SMD 0.791). Conclusion: The results of this systematic review support the conclusion that utilizing pain education strategies in conjunction with interventions provided by physical therapists demonstrates a moderate to large effect sizes on pain and disability constructs but lack pooled statistical significance.